A multiproduct batch plant design model incorporating production planning and scheduling decisions under a multiperiod scenario - Fumero, Yanina (2015)
The goal of this work is to propose a multiperiod mixed-integer linear programming model that integrates several decisions about multistage multiproduct batch plants. Usually, plant design was solved without considering operation decisions. The proposed approach considers not only production planning but also scheduling decisions. The time horizon consists of several periods in which deterministic variations in prices, products demand limits, costs, and raw materials availability are taken into account. The plant operates using different production campaigns along each time period. The proposed model allows not only finding the optimal plant structure (unit sizes and its duplication in parallel in each stage), but also the detailed production planning in every time period. In this way, this work enables to assess the trade-offs between the different involved decision levels, taking into account fluctuations along the time horizon.